Efektivitas Konseling Person Centered Expressive Art Therapy Terhadap Kesejahteraan Emosional Santri - Zulfa Nadia Ar-Ridlwany; Feida Noor Laila Isti’adah; Gian Sugiana Sugara (GUIDING WORLD (BIMBINGAN DAN KONSELING), 2026)
This study aimed to examine the effectiveness of Person-Centered Expressive Art Therapy (PCEAT) counseling in improving the emotional well-being of students. Emotional well-being refers to individuals’ affective evaluation of their lives, consisting of positiveaffect and negative affect dimensions. The study employed a quantitative approach using a Single Subject Research (SSR) experimental design with an A-B-A pattern. The participants consisted of three students identified as having low levels of emotional well-being based on the Emotional Well-Being Scale (EWBS) developed by Şimşek (2011). The intervention was conducted through five counseling sessions based on expressive art activities to facilitate the expression and understanding of emotional experiences. Data were analyzed using visual analysis and the Percentage of Non-Overlapping Data (PND) technique to examine changes across baseline and intervention phases. The results indicated an increase in emotional well-being scores among all participants after the intervention. These findings suggest that Person-Centered Expressive Art Therapy is effective in enhancing students’ emotional well-being and can serve as an alternative counseling approach in Islamic boarding school settings.